(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to analyse the growth rate and contribution of Motor Vehicle Tax (PKB), Motor Vehicle Transfer Duty (BBNKB), and Motor Vehicle Fuel Tax (PBBKB) to the Local Own-Source Revenue (PAD) of Maluku Province for the period 2020–2024. The method used is quantitative descriptive analysis utilising secondary data in the form of Budget Realisation Reports obtained from the Maluku Provincial Revenue Agency. The analysis was conducted by calculating the growth rates and contribution ratios of each type of tax to PAD. The results of the study indicate that the growth rates of PKB, BBNKB, PBBKB, and PAD fluctuated during the study period. The highest average growth rate was achieved by PBBKB at 13.62%, followed by PKB at 6.65%, PAD at 6.42%, and BBNKB at 2.25%. In terms of contribution, PBBKB was the largest contributor to PAD with an average contribution of 26.05%, followed by PKB at 17.70% and BBNKB at 10.62%. These findings indicate that PBBKB is the most dominant source of revenue in supporting the Provincial Own Revenue (PAD) of Maluku Province, whilst PKB acts as a relatively stable source of revenue. Therefore, the local government needs to optimise the management of local taxes through improved taxpayer compliance, strengthening the tax administration system, and utilising technology to enhance the effectiveness of tax collection in order to support fiscal autonomy and regional development.